2021
DOI: 10.1111/abac.12217
|View full text |Cite
|
Sign up to set email alerts
|

Stock and Bond Return Comovement as a Different Way to Assess Information Content: The Case of Debt Covenant Violation Disclosures

Abstract: We propose a supplementary way to assess the information content of a financial statement disclosure based on the comovement of asset returns in different markets in response to information that has price implications for both. The influence of a signal that strongly influences at least two asset markets measures a dimension of information content less clearly reflected in single-market responses. We apply our method to debt covenant violation (DCV) disclosures. These are the outcome of a debt renegotiation wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Stocks and bonds are regarded as important financial assets in the securities market, and they will interact with each other. Griffin et al [34] found a two-way risk spillover effect between the stock market and the corporate bond market.…”
Section: Control Variablesmentioning
confidence: 99%
“…Stocks and bonds are regarded as important financial assets in the securities market, and they will interact with each other. Griffin et al [34] found a two-way risk spillover effect between the stock market and the corporate bond market.…”
Section: Control Variablesmentioning
confidence: 99%